Pengaruh Nafas Dalam dan Posisi Terhadap Saturasi Oksigen dan Frekuensi Nafas Pada Pasien Asma - Anita Yulia; Dahrizal Dahrizal; Widia Lestari (Poltekkes Kemenkes Bengkulu, 2019)
Asthma is a disorder of chronic inflammation of the airways which causes shortness of breath so that in clinical conditions there will be a decrease in oxygen saturation. One intervention that can be done in asthma patients to maximize pulmonary ventilation is diaphragmatic breathing exercises. This study aimed to determine the effect of deep breath and position on the oxygen saturation (SpO2) and respiratory rate (RR)in asthma patients. This study used a quasi-experimental design with pretest-posttest with control group. In this study the sample was taken using consequtives sampling with 15 people in one group and the entire study sample was 30 people. Measuring the SpO2 value of patients using Oxymetri and the frequency of breathing using a stopwatch for one minute. Intervention of deep breathing techniques and positioning and after observation for 30 minutes. The analysis used the Mann Whitney test. The results of the study showed the influence of deep breathing intervention and position on the SpO2 value of asthma patients (P Value = 0.001) and there was influence of deep breathing intervention and position on the RR value of asthma patients (P Value = 0.001). Asthma can be realized by proper management of asthma. Appropriate management includes making lung function close to normal, preventing recurrence of the disease to prevent death.